Investigating the microstructure and mechanical properties of L-shaped structure of TM-B9 HSLA steels using WAAM process - Rakesh Chaudhari; Jash Modi; Souradeep Dutta; Vatsal Vaghasia; Subhas Das; Jay Vora; Subraya Krishna Bhat (Results in Surfaces and Interfaces)
Gas metal arc welding (GMAW)-based Wire-arc additive manufacturing (WAAM) process has been employed in the present study for fabrication of the L-shaped wall structure of TM-B9 low alloy steel on mild steel substrate plate. A 100-layered wall was built with optimal process parameters (voltage of 21 V, travel speed of 5 mm/s, wire feed speed of 6.5 mm/s, and gas flow rate of 15 L/min), which was detected with seamless fusion and without disbonding. The L-shape wall was investigated at different locations (corner joint, horizontal, and vertical direction). Microstructure at bottom, middle, and top regions has revealed fairly rounded structure of grains, the interface dendritic structures with rounded grains, and fairly dendritic and finer granular structure, respectively. The examined tensile test results have shown the average UTS of 1160.41 ± 34.92 MPa, YS of 927.1 ± 28.2 MPa for horizontal specimens, while UTS of 1039.81 ± 56.90 MPa, YS of 830.0 ± 46.4 MPa for vertical specimens. The experimental findings reveal that the UTS, YS, and EL values of the WAAM-produced components exceed those of conventional TM-B9 low alloy steel, indicating superior tensile performance. Impact test results showed uniform acceptable values for both vertical and horizontal specimens. MH evaluation was carried out at the corner joint structure, and built direction of the built plate has shown uniformity across the different layers.